Factors associated with masseter muscle quality assessed from ultrasonography in community-dwelling elderly individuals: A cross-sectional study. (May 2019) - Yamaguchi, K.; Tohara, H.; Hara, K.; Nakane, A.; Yoshimi, K.; Nakagawa, K.; Minakuchi, S.
Highlights: Masseter muscle thickness correlates with masseter muscle echo intensity. Masseter muscle echo intensity correlates with grip strength and walking speed. Masseter muscle echo intensity does not correlate with tooth-loss. Masseter muscle echo intensity is easily determined ultrasonographically. Masseter muscle echo intensity may be predictive of dynapenia. Abstract: Background: Associations between masseter muscle thickness(MMT) and limb muscle thickness, and between grip strength and MMT, as well as tooth-loss, have been reported previously. The previous study also showed that masseter muscle mass could be a better marker of sarcopenia than psoas muscle mass. Although the association between MMT and muscle strength is also known, the quality of the masseter muscle were not assessed in detail previously. We examined the relationship of masseter muscle echo intensity (MMEI) with skeletal muscle, physical function, and nutrition status, in order to determine whether MMEI could be a good indicator of these parameters. Methods: We assessed 139 community-dwelling elderly individuals (men: 65, women: 74). Age, body mass index (BMI), skeletal muscle mass index, grip strength, walking speed, calf circumference, tooth-loss (Eichner classification), occlusal force, MMT, and MMEI were obtained. In multiple regression analysis, MMEI were set as dependent variables. Results: Multiple regression analysis revealed BMI (p < 0.05), grip strength (p < 0.01), walking speed (p < 0.01), and MMT (p < 0.01) as factors with significant association with MMEI. Conclusions: MMT is related to occlusal force and MMEI. MMEI was related strongly to grip strength and walking speed, but not to tooth-loss. However, MMEI, which is easily determined ultrasonographically, could be a good indicator of grip strength and walking speed, and thus may be predictive of dynapenia.